Structural transformations of carbon chains inside nanotubes - Warner, J; Rümmeli, M; Bachmatiuk, A; Büchner, B (2010)
In situ aberration-corrected high-resolution transmission electron microscopy is used to examine the structural transformations of carbon chains that occur in the interior region of carbon nanotubes. We find electron-beam irradiation leads to the formation of two-dimensional carbon structures that are freely mobile inside the nanotube. The inner diameter of the nanotube influences the structural transformations of the carbon chains. As the diameter of the nanotube increases, electron-beam irradiation leads to curling of the chains and eventually the formation of closed looped structures. The closed looped structures evolve into spherical fullerenelike structures that exhibit translational motion inside the nanotubes and also coalesce to form larger nanotube structures. These results demonstrate the use of carbon nanotubes as test tubes for growing small carbon nanotubes within the interior by using only electron-beam irradiation at 80 kV. © 2010 The American Physical Society.